Pengaruh Konseling Keluarga Berencana Menggunakan Media Audiovisual Terhadap Penggunaan Alat Kontrasepsi IUD - Umar, Siskawati; Nurdin, St.Surya Indah; Zakaria, Fatmah; Mulyaningsih, Sri (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2025)
More than 95% of postpartum women want to delay the next pregnancy or do not want to get pregnant again but do not use contraception, resulting in unintended pregnancy which ends in risky pregnancy or unsafe abortion. The purpose of this study was to determine the effect of family planning counseling using audiovisual media on the use of IUD contraceptives in postpartum women. The research method used was Quasy Eksperiment. Subjects were selected using consecutive sampling with a total sample of 64 people divided into control and intervention groups. Data analysis using Chi Square with a significance level of p value <0.05. The results of statistical tests showed that the proportion of IUD contraceptive use in postpartum women in the intervention group was greater 17 (53.1%) than the control group 8 (25%). Counseling using audiovisual media in postpartum women has a significant effect on the use of IUD contraceptives (p < 0.05). Family planning counseling using audiovisual media effectively influences the use of IUD contraceptives in postpartum women.